Concussion in Women's Flat-Track Roller Derby - Stockbridge, Melissa D.; Keser, Zafer; Newman, Rochelle S. (Frontiers in Neurology, 2022)
Concussions are common among flat-track roller derby players, a unique and under-studied sport, but little has been done to assess how common they are or what players can do to manage injury risk. The purpose of this study is to provide an epidemiological investigation of concussion incidence and experience in a large international sampling of roller derby players. Six hundred sixty-five roller derby players from 25 countries responded to a comprehensive online survey about injury and sport participation. Participants also responded to a battery of psychometric assessment tools targeting risk factors for poor injury recovery (negative bias, social support, mental toughness) and players’ thoughts and feelings in response to injury. Per 1000 athletes, 790.98 concussions were reported. Current players reported an average of 2.2 concussions, while former players reported 3.1 concussions. However, groups were matched when these figures were corrected for differences in years of play (approximately one concussion every two years). Other frequent injuries included fractures in extremities and upper limbs, torn knee ligaments, and sprained ankles. We found no evidence that players’ position, full-contact scrimmages, or flooring impacted number of concussions. However, neurological history and uncorrected vision were more influential predictors of an individual’s number of concussions during roller derby than years of participation or age, though all four contributed significantly. These findings should assist athletes in making informed decisions about participation in roller derby, though more work is needed to understand the nature of risk.